Health is wealth : health progrmme - Mackenzie, James; Haldane, William S. ([Scotland : Industrial Health Education Council], 1926)
1926 1926 1920s 16 pages 9 List of Subscriptions UNDER SECRETARY FOR MINES — Allocation from Miners' Welfare Fund, £400 0 0 THE CARNEGIE UNITED KINGDOM TRUST, 250 0 0 PRUDENTIAL ASSURANCE CO., 105 0 0 DENTAL BOARD OF UNITED KINGDOM, 100 0 0 THE ASSOCIATION OF JUTE SPINNERS AND MANUFACTURERS, 70 0 0 Sir JOHN FINDLAY, Bart., 50 0 0 WM. WHITELAW, Esq., 50 0 0 Sir W. S. HALDANE (1924), 25 0 0 Sir MALCOLM SMITH (1924), 25 0 0 THOMAS BARCLAY, Esq 25 0 0 G. H. LAW, Esq., 25 0 0 Sir WM. S. HALDANE, 25 0 0 JOHN FRASER, Esq., 21 0 0 GENERAL ACCIDENT FIRE & LIFE ASSURANCE CORPORATION, Ltd. 21 0 0 EDINBURGH CORPORATION COMMON GOOD, 21 0 0 WM. YOUNGER & Co., Ltd., 10 10 0 W.C. TEACHER, Esq., 10 10 0 NESTLES' MILK CO. (1924) 10 0 0 Sir PATRICK J. FORD, 10 0 0 SCOTTISH CO-OPERATIVE WHOLESALE SOCIETY, 10 0 0 Sir D.M. STEVENSON, 10 0 0 Dr. BARBOUR, 10 0 0 JAMES FINDLAY & Co., Ltd., 10 0 0 Sir F. C. GARDINER, 10 0 0 SCOTTISH CO-OPERATIVE WHOLESALE SOCIETY, 10 0 0 GEO. A. MITCHELL, Esq., 10 0 0 NESTLE & ANGLO-SWISS CONDENSED MILK Co., 10 0 0 Dr. T.G. NASMYTH, 5 5 0 R.W. WALLACE, Esq., 5 5 0 SCOTTISH ALLIANCE OF EMPLOYERS IN THE PRINTING AND KINDRED TRADES, 5 5 0 GUARDIAN ASSURANCE CO., 5 5 0 BLOCH BROS., 5 5 0 L. V. CURTIS (English Fund), 5 5 0 The Right Hon. LORD SALVESEN, 5 0 0 D.M. BROWN, Esq., 5 0 0 T.D. HUNTER, Esq., 5 0 0 CHARLES. PRICE, Esq., 5 0 0 A. R. DICK, Esq..... 5 0 0 A.F.P. 5 0 0 R. C. GREIG & Co. 5 0 0 C. & J. ROBERTSON, Ltd., 5 0 0 D. M'COWAN, Esq., 5 0 0 A. R. DICK, Esq., 5 0 0 Sir MALCOLM SMITH, 5 0 0 DAVIES, DUNN & CO., 3 3 0 Sir ROBERT USHER, Bart. (1924), 3 0 0 Miss E. SHIELS, 3 0 0 Sir ROBERT USHER, Bart., 3 0 0 J. & W. BROWN, 2 2 0 TURNBULL & SPEARS, 2 2 0 T. FORBES MACLENNAN, Esq., 2 2 0 GEORGE WATERSTON & SON, 2 2 0 J. WILSON BRODIE, Esq., 2 2 0 H.C. HUTCHISON, Esq., 2 2 0 SCOTTISH MOTOR TRACTION Co., 2 2 0 T. & J. BERNARD, Ltd., 2 2 0 200/B/3/2/C693/1/48